2008
DOI: 10.1002/pros.20752
|View full text |Cite
|
Sign up to set email alerts
|

RAD001 (Everolimus) inhibits growth of prostate cancer in the bone and the inhibitory effects are increased by combination with docetaxel and zoledronic acid

Abstract: INTRODUCTION-mTOR activity is increased in advanced prostate cancer (CaP) as a result of a high rate of PTEN mutations. RAD001 (Everolimus) is a new orally available mTOR inhibitor. The objective of our study was to evaluate the effects of RAD001 on the growth of CaP in the bone, both alone and in combination with docetaxel and zoledronic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 39 publications
(43 reference statements)
1
48
0
Order By: Relevance
“…However, when docetaxel was used in combination with dasatinib, the dose resulted in significant decreases in PSA levels beyond those seen with the administration of dasatinib alone. We have previously seen this increased efficacy with the use of other pharmaceuticals in combination with docetaxel over either agent alone (Brubaker et al, 2006;Morgan et al, 2008). In addition, src inhibition has been reported to increase sensitivity of other advanced cancers to several already used chemotherapies and specifically to docetaxel resistance (Yezhelyev et al, 2004;Han et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, when docetaxel was used in combination with dasatinib, the dose resulted in significant decreases in PSA levels beyond those seen with the administration of dasatinib alone. We have previously seen this increased efficacy with the use of other pharmaceuticals in combination with docetaxel over either agent alone (Brubaker et al, 2006;Morgan et al, 2008). In addition, src inhibition has been reported to increase sensitivity of other advanced cancers to several already used chemotherapies and specifically to docetaxel resistance (Yezhelyev et al, 2004;Han et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…A total of 48 animals were injected, and 4 weeks after the tumour cell injection animals that had serum PSA level 40.6 ng ml À1 (IMx Total PSA Assay) were randomised into four groups using the following design: (1) a control group receiving placebo treatment (n ¼ 8, PSA -4.376 ± 1.13 ng ml À1 (mean ± s.e.m. )); (2) a group receiving docetaxel at 5 mg kg À1 (Morgan et al, 2008; n ¼ 7, PSA -6.507±1.38 ng ml À1 ); (3) a group receiving dasatinib only at 50 mg kg À1 (n ¼ 8, PSA -6.136 ± 0.99 ng ml À1 ) and (4) a group receiving a combination of dasatinib 50 mg kg À1 and docetaxel 5 mg kg À1 (n ¼ 8, PSA -6.045±1.098 ng ml À1 ). There were no differences in enrolment PSA levels (ANOVA, P ¼ 0.5834).…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Activation of the PI3K/Akt/mTOR pathway has recently been implicated in resistance to docetaxel (Qian et al 2010), and combining PI3K/Akt/mTOR pathway inhibitors with docetaxel has demonstrated enhanced activity in a variety of preclinical models (Morgan et al 2008, Fung et al 2009, Dubrovska et al 2010, Qian et al 2010, Maira et al 2012b, Morikawa et al 2012. The enhanced efficacy of BEZ235 with docetaxel was shown to be a result of BEZ235-induced reduction of CD133C/CD44C tumor progenitor cells, and docetaxel-induced reduction of the tumor bulk, which resulted in near complete tumor regression in a mouse prostate cancer xenograft model (Dubrovska et al 2010).…”
Section: Combination With Chemotherapymentioning
confidence: 99%
“…In fact, in vitro and in vivo studies have demonstrated that ZA plus Everolimus (RAD001) augment the growth-blocking effect seen with either drug alone. 26,27 Clinical trials have indicated a reduced incidence of skeletalrelated events in men with hormone-refractory metastatic PC treated with ZA. 5 Hence, it has been argued that ZA may directly influence metastatic tumor spread.…”
Section: Discussionmentioning
confidence: 99%